2у-2 + у+3 =5 у+3      у-3

2у-2 + у+3 =5 у+3      у-3
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{(2y-2)(y-3)}{(y+3)(y-3)} + \frac{(y+3)^2}{(y-3)(y+3)} = \frac{2y^2-6y-2y+6+y^2+6y+9}{(y-3)(y+3)} =\frac{3y^2-2y+15}{(y-3)(y+3)}=5[/latex] [latex]\frac{3y^2-2y+15}{(y-3)(y+3)}=5[/latex] [latex]\frac{3y^2-2y+15}{(y-3)(y+3)}- \frac{5y^2-45}{(y-3)(y+3)} =0[/latex] [latex]\frac{3y^2-2y+15}{(y-3)(y+3)}- \frac{5y^2-45}{(y-3)(y+3)} = \frac{-2y^2-2y+60}{(y-3)(y+3)} =0[/latex] [latex] 2y^2+2y-60=0[/latex] x1=5,x2=-6
Не нашли ответ?
Ответить на вопрос
Похожие вопросы